2015
DOI: 10.1007/s12565-015-0315-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, topographic and morphometric features of femoral cam-type deformity: changes in relation to age and gender

Abstract: Femoroacetabular impingement (FAI) syndrome is a frequent cause of pain and in recent years considered to be a precursor of premature hip osteoarthritis. The structural abnormalities which characterize FAI syndrome, such as the cam-type deformity, are associated with morphological alterations that may lead to hip osteoarthritis. The aim of this study was to determine the prevalence and topographic and morphometric features of the cam deformity in a series of 326 femur specimens obtained from a Mexican populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…No correlation between age and α -angle was found. These observations are in line with results from several other studies [ 25 , 30 , 34 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No correlation between age and α -angle was found. These observations are in line with results from several other studies [ 25 , 30 , 34 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, assessment of cam deformities has often been performed by measuring α -angles at the anterior aspect of the femoral head-neck junction [ 5 , 21 , 29 31 ]. However, several studies have shown that the area of maximum extension of the cam deformity may vary between patients and that the greatest loss of head-neck asphericity is present at either the anterior aspect of the head-neck junction or the anterior-superior surface [ 32 34 ]. As a result, a straight axial X-ray of the femoral head-neck junction may underproject the maximum extension of the cam deformity in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior studies have suggested that anatomic differences in female hips, such as a lower prevalence of cam-type deformities, may help protect against some types of hip injuries. 21,22,29,36,39,41 Another important consideration in sex-related injury discrepancies is the impact of the female athlete triad, which may also help explain the increased number of overuse injuries in female athletes. 27 When analyzing the length of time lost and the severity of injury, some interesting patterns emerge.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm previous data reported by our research team in contemporary osteological specimens with known sex and age. 32 Nonetheless, these suggestions should be confirmed with more comprehensive and longitudinal studies.…”
Section: Discussionmentioning
confidence: 98%